(untitled) - Ngo, Thi Phuong Dung (Wageningen, 2004)
The present thesis addresses the problem of poor and variable quality of traditional starter tablets by understanding and quantifying the impact of microflora in these starters, concentrating on mycelial fungi and yeasts and by assessing the option of preparing stable mixed cultures of selected compatible strains.
Keywords: Fungal enzymes,Wine,Enzym nấm,Rượu